Forecasting peak electricity demand for Los Angeles considering higher air temperatures due to climate change. (15th February 2019) - Burillo, Daniel; Chester, Mikhail V.; Pincetl, Stephanie; Fournier, Eric D.; Reyna, Janet
Highlights: Peak electricity demand projected to increase by 0.2–6.5 GW (2–51%) by 2060. Rising air temperatures projected to increase peak demand by 4–8% by 2060. Maximum temperatures in inland regions are projected to reach 54 °C (129 °F). Shared wall housing can reduce peak demand by up to 50% per building. Air conditioner SEER ratings effective for annual demand, but not peak demand. Abstract: Los Angeles County (LAC) is a large urbanized region with 9.7 million residents (as of 2010) and aging infrastructure. Population forecasts indicate that LAC will become home to an additional 1.2–3.1 million residents through 2060. Additionally, climate forecasts based upon representative concentration pathway (RCP) scenarios 4.5 and 8.5 indicate that average air temperatures will increase by 1–4 °C (2–7 °F) in the region. Both of these factors are expected to result in higher summertime peak electricity demand due to growth in the number of buildings, the percentage of installed air conditioners (ACs), and the additional cooling load on those air conditioners. In order to understand potential power reliability issues, and support infrastructure planning efforts, a long-term peak demand forecast was developed using hourly residential and commercial (R&C) building energy models. Peak hour electricity demand was estimated to increase from 9.5 to 12.8 GW for R&C sectors, to 13.0–17.3 GW (2–36%) and 14.7–19.2 GW (16–51%) by 2060 for the population forecasts from the California Department of Finance and the Southern California Association of Governments respectively. While marginal increases in ambient air temperature due to climate change accounted for only 4–8% of future increases in peak demand, differences in annual maximum temperatures within the 20-year periods affected results by 40–66% indicating a high sensitivity to heat waves. Population growth of at least 1 million people is anticipated to occur mostly in the northern cities of Palmdale, Lancaster, and Santa Clarita, bringing an additional 0.4–1 GW of peak demand in those regions. Building and AC efficiency are anticipated to improve as national and state efficiency standards increase, and as older, less efficient units are replaced; this could offset some of the projected increases in peak demand. Additionally, development of shared wall, multi-family dwelling units could enable population growth of up to 3 million people without increasing peak demand.